Unraveling predictors affecting compliance to MRI in Parkinson's disease. Issue 8 (August 2015) - Cacciari, Claudia; Pellicano, Clelia; Cravello, Luca; Assogna, Francesca; Piras, Fabrizio; Paravia, Patrizia; Gili, Tommaso; Iorio, Mariangela; Stefani, Alessandro; Pierantozzi, Mariangela; Caltagirone, Carlo; Pontieri, Francesco E.; et al.
Abstract: Introduction: Magnetic resonance imaging (MRI) is a sensitive, noninvasive and widely available technique for studying Parkinson's disease (PD) from both research and clinical perspective. Several issues may physically impede execution of MRI. Moreover, the severity of motor or non-motor symptoms of PD might reduce compliance to MRI. Here we investigated predictors affecting compliance to MRI in PD patients. Methods: Two-hundred-thirty-six PD patients underwent clinical, neuropsychological and neuropsychiatric investigations. Accordingly to their ability/inability to perform MRI scan, they were divided into 3 groups. Forty-two patients had physical incompatibility to MRI (PI); 51 patients refused to undergo scan during the MRI evaluation session (RR); 143 patients accepted to undergo and successfully completed MRI (SP). Multivariate/Univariate Analyses of Variance, followed by Bonferroni's post-hoc comparisons, were used to assess differences among groups. To identify predictors of compliance to MRI scan in the whole PD sample (SP vs. RR + PI) we carried out a logistic regression analysis. Results: PI subjects were significantly older, had higher UPRDRS-III score, received lower daily dopamine agonist doses, and displayed worse cognitive performances than SP. RR subjects had significantly higher anxiety severity than SP. Lower daily dopamine agonist equivalents and higher anxiety scores were the significant whole predictors of not compliance to MRI in the logistic regression analysis. Conclusions: These results show that demographic, neuropsychological and neuropsychiatric features may limit compliance to MRI in PD, and provide valuable aid for setting and interpreting research and clinical MRI studies in PD. Highlights: We investigated predictors affecting compliance to MRI in PD patients. Refusing MRI was associated with anxiety symptoms. Physical incongruity to MRI was associated with increased age and clinical symptoms. Some clinical features may limit compliance to MRI in PD.